Mapping of control measures to prevent secondary transmission of STEC infections in Europe during 2016 and revision of the national guidelines in Norway. (2019) - Veneti, L.; Lange, H.; Brandal, L.; Danis, K.; Vold, L.
Abstract: In 2016, we reviewed preventive control measures for secondary transmission of Shiga-toxin producing Escherichia coli (STEC) in humans in European Union (EU)/European Free Trade Association (EEA) countries to inform the revision of the respective Norwegian guidelines which at that time did not accommodate for the varying pathogenic potential of STEC. We interviewed public health experts from EU/EEA institutes, using a semi-structured questionnaire. We revised the Norwegian guidelines using a risk-based approach informed by the new scientific evidence on risk factors for HUS and the survey results. All 13 (42%) participating countries tested STEC for Shiga toxin ( stx ) 1, stx2 and eae (encoding intimin). Five countries differentiated their control measures based on clinical and/or microbiological case characteristics, but only Denmark based their measures on routinely conducted stx subtyping. In all countries, but Norway, clearance was obtained with ⩽3 negative STEC specimens. After this review, Norway revised the STEC guidelines and recommended only follow-up of cases infected with high-virulent STEC (determined by microbiological and clinical information); clearance is obtained with three negative specimens. Implementation of the revised Norwegian guidelines will lead to a decrease of STEC cases needing follow-up and clearance, and will reduce the burden of unnecessary public health measures and the socioeconomic impact on cases. This review of guidelines could assist other countries in adapting their STEC control measures.